URNCST Journal 2022
DOI: 10.26685/urncst.348
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Amyotrophic Lateral Sclerosis (ALS): An Updated Systematic Review

Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease impacting the voluntary motor nervous system. While the origin of ALS remains unclear, existing literature suggests multifactorial pathogenesis. Most cases appear sporadically, implicating the existence of environmental factors, while others suggest an underlying genetic mechanism. This study aims to summarize risk factors associated with the onset and progression of ALS. Methods: Three reviewers searched Medline datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…(30) However, in ALS cases, toxic substances, including nicotine and formaldehyde, or poisoning contamination by heavy metals and insecticides are a possible explanation of how smoking increases the risk of ALS (17). Results from our study indicate that smoking increases the risk of developing ALS, which comes to agreement with other studies (13,(31)(32)(33). A previous ALS epidemiological study in Cyprus by Demetriou et al (34) found a statistically significant association between male and female cases (34), supporting our outcome with regard to smoking.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(30) However, in ALS cases, toxic substances, including nicotine and formaldehyde, or poisoning contamination by heavy metals and insecticides are a possible explanation of how smoking increases the risk of ALS (17). Results from our study indicate that smoking increases the risk of developing ALS, which comes to agreement with other studies (13,(31)(32)(33). A previous ALS epidemiological study in Cyprus by Demetriou et al (34) found a statistically significant association between male and female cases (34), supporting our outcome with regard to smoking.…”
Section: Discussionsupporting
confidence: 90%
“…It is believed that sALS is equally influenced by the interaction of multiple genes (polygenic traits) and environmental risk factors (11). Numerous studies have focused on the environmental risk factors that are positively associated with ALS (12)(13)(14)(15)(16)(17)(18). However, dietary factors such as vitamin E supplements and polyunsaturated fatty acids consumption, as well as type 2 diabetes, have shown an inverse association with ALS since they were associated with a lower risk of ALS (11,16,19).…”
Section: Introductionmentioning
confidence: 99%